Silicon addition improves plant productivity and soil nutrient availability without changing the grass:legume ratio response to N fertilization - Xu, Danghui (Sci Rep, 2020)
Silicon (Si) plays an important role in plant nutrient capture and absorption, and also promotes plant mechanical strength and light interception in alpine meadows. In this study, we conducted a field experiment to examine the effect of nitrogen (N) application, with (N + Si) and without Si (N-only), on the potential for soil nutrient and the growth of grass and legume plant functional types (PFTs) in an alpine meadow. It was found that N + Si resulted in higher soil nutrient contents, leaf N and P concentrations, abundance and biomass of legume and grass PFTs than N-only. The aboveground biomass of grass (598 g m(−2)) and legume (12.68 g m(−2)) PFTs under 600 kg ha(−1) ammonium nitrate (NH(4)NO(3)) per year addition with Si was significantly higher than that under the same level of N addition without Si (515 and 8.68 g m(−2), respectively). The grass:legume biomass ratio did not differ significantly between the N + Si and N-only. This demonstrates that Si enhances N fertilization with apparently little effect on grass:legume ratio and increases plant-available nutrients, indicating that Si is essential for the plant community in alpine meadows.